Performance of Rapid Sand Filter Dual Media for Microplastic Removal in the Water: The Effect of Microplastic Size and Effective Size of Filter Media - Wulandari, Marita; Marpaung, Kevin; Prasaningtyas, Asri; Yorika, Rahmi; Harfadli, Muhammad Ma'arij; Zulfikar, Ainun (Journal of Community Based Environmental Engineering and Management, 2024)
Microplastics (MPs) significantly damage the environment and human health, leading to a growing global concern. MPs have been detected not only in the natural environment but also in the drinking water treatment process. One of the configurations of the drinking water treatment unit is filtration. Only a few research studies have been published on microplastic removal in the water system. This study was conducted to determine the performance of a rapid sand filter (RSF) in removing microplastics in water with a variation in the effective size (ES) of silica sand and microplastic size. In this study, microplastics are artificially made with size variations of < 400 μm and >400 μm. The filtering uses two variations in the adequate size (ES) of silica sand, namely 0.4 mm and 0.7 mm. At the same time, anthracite is only a control variable with ES = 0.69 with a flow speed of 4 m / h and an observation time of 30, 60, 90, and 120 minutes. The results show that the filter media ES 0.4 has the highest efficiency values of 91.30% for the microplastic size MPs <400 µm and 95.80 % for the larger microplastic >400 µm. In addition, the average percentage removal of ES 0.7 mm was 77.24 % for the size of MPs <400 µm and 95.77% for the size of Mps >400 µm. Gaining insight into the mechanisms involved in removing microplastics from drinking water is essential for developing more effective techniques for eliminating them.